Centro intergeneracional - Sandoval Guano, María Isabel (2018)
In the following work of Titulación, Intergenerational Center, a social welfare equipment located in La Mariscal. An equipment focused on the care of the elderly is proposed with a residence where an adequate space for the daily activities of this vulnerable group of society is given. In order to propose an equipment that solves problems of the near environment and responds to the needs of the users, a preliminary investigation was made of several urban, architectural and environmental parameters that positively affect the development of the project. It focuses on the resolution of a new architectural program that proposes the interaction between the elderly and children in order to achieve mutual benefit. The workshops that take place in the equipment allow the older adult to interact daily and in a controlled way with the children when carrying out activities that allow the development of both generational groups.